Desenvolvimento e análise de métodos de reconstrução de trajetória de aeronaves - Plinio Marvila Fagundes (2007)
Flight path reconstruction comprises vehicle position and attitude estimation, during a certain period of time, from a limited set of measurements. In this work this procedure is viewed as an optimization problem related to the search for optimal curves, in a mean square sense, corresponding to the measured times-series, acquired from flight test data of fixed wing aircraft. The information available to execute the procedure corresponds to data from an inertial measurement unit (IMU), together with global positioning system data (GPS). As a by-product of the flight path reconstruction activity the instruments biases are also estimated, which is essential in the posterior aircraft mathematical model identification process. Thirteen optimization algorithms are present and analysed. Their performance is evaluates in three different scenarios related to maneuver type, noise contamination and number of measured variables.